ANALISIS PEMBERIAN KOMPENSASI GURU SWASTA SMP PADA PERGURUAN ADVENT PASIR PUTIH DESA BARU KECAMATAN SIAK HULU KABUPATEN KAMPAR - Butar-Butar, Frend; Syarfan, La Ode (UIR PRESS, 2021)
This study aims to identify and explain the provision of teacher compensation and its obstacles at the Pasir Putih Adventist College, Baru Village, Siak Hulu District, Kampar Regency. The type of research is a descriptive survey with a quantitative approach. The research data was obtained secondary and primary with the internal population from all middle school teachers right/index and the Principal of the Pasir Putih Adventist School, amounting to 9 people. The entire population was used as a research sample with a census sampling technique. Data analysis is the process of systematically searching and compiling data obtained from questionnaires, interviews, and observations. Based on the results of the previous data analysis, it can be concluded that the results of the study are as follows: Compensation for the teachers of the Pasir Putih Adventist Middle School is good or 77.8%. These results are in accordance with the responses submitted by each research indicator, namely the direct compensation indicator received by the Pasir Putih Adventist Middle School teacher which is in the good category. The teachers have received salaries, incentives, and allowances provided by the foundation every month. Then this indirect compensation indicator is in the good category. These results certainly have provided an illustration that the compensation applied by the foundation in the form of indirect compensation has been very good, so it is hoped that this incentive indicator can also have a good impact on teacher achievement. The obstacle in providing compensation is that there is no assessment in providing incentives and family gathering activities or entertaining teachers from the tiredness of teaching and learning activities by taking walks (picnics), so that teachers to get together have to pay their own expenses.